2017
DOI: 10.1016/j.bmc.2017.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Novel pyridyl nitrofuranyl isoxazolines show antibacterial activity against multiple drug resistant Staphylococcus species

Abstract: A novel series of pyridyl nitrofuranyl isoxazolines were synthesized and evaluated for their antibacterial activity against multiple drug resistant (MDR) Staphylococcus strains. Compounds with piperazine linker between the pyridyl group and isoxazoline ring showed better activity when compared to compounds without the piperazine linker. 3-Pyridyl nitrofuranyl isoxazoline with a piperazine linker was found to be more active than corresponding 2-and 4-pyridyl analogues with MICs in the range of 4-32µg/mL against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Further investigations showed that 3‐pyridyl‐nitrofuranyl‐isoxazoline, when linked to a piperazine linker, is more potent than corresponding 2‐ and 4‐pyridyl derivatives having MIC values between 4 and 32 μg mL −1 against MDR Staphylococcus strains. Among the synthesized compounds, 67 and 68 were tested and found to be potent toward S. aureus and Staphylococcus epidermidis with MICs ranging from 8 to 32 μg mL −1 for 67 and 4 to 16 μg mL −1 for 68 , compared with the reference antibiotic drug nitrofurantoin (MIC: 16 μg mL −1 ) [15] . Kudryavtseva et al.…”
Section: Pharmacological Profile Of Isoxazoline Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations showed that 3‐pyridyl‐nitrofuranyl‐isoxazoline, when linked to a piperazine linker, is more potent than corresponding 2‐ and 4‐pyridyl derivatives having MIC values between 4 and 32 μg mL −1 against MDR Staphylococcus strains. Among the synthesized compounds, 67 and 68 were tested and found to be potent toward S. aureus and Staphylococcus epidermidis with MICs ranging from 8 to 32 μg mL −1 for 67 and 4 to 16 μg mL −1 for 68 , compared with the reference antibiotic drug nitrofurantoin (MIC: 16 μg mL −1 ) [15] . Kudryavtseva et al.…”
Section: Pharmacological Profile Of Isoxazoline Derivativesmentioning
confidence: 99%
“…Various other nitrogen‐containing five‐membered heterocyclic compounds such as triazole, [7–8] imidazole[1,2‐ a ]pyridine, [9–11] etc., have also been explored for their biological activity. Isoxazoline‐based molecules have attracted considerable attention because of their ability to generate various cyclic and acyclic compounds and diverse biological profiles such as anti‐inflammatory, [12] anticancer, [13] antifungal, [14] antibacterial, [15] antioxidant, [16] anti‐asthmatic, [17–18] antinociceptive, [19–20] hypoglycemic, [21] antimalarial, [22] antituberculosis, [23] and antithrombotic activity [24] . Some compounds with the isoxazoline pharmacophore are found to be highly active and recommended in drug discovery [6,25] such as roxifiban acetate ( 2 ) acting as glycoprotein IIb/IIIa antagonists, [26] ( S , R )‐3‐(4‐hydroxyphenyl)‐4,5‐dihydro‐5‐isoxazole acetic acid methyl ester (ISO‐1; 3 ) acting as an inhibitor of the proinflammatory cytokine MIF, [27–28] and glucose‐based spiro‐isoxazolines 4 acting as antidiabetic compounds [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Isoxazolines can be converted into various synthetic units, such as hydroxy ketones [ 7 ], amino alcohols [ 8 ], β-hydroxynitrile [ 9 ], and masked aldols [ 10 ], and be used as synthetic equivalent of 1,3-dicarbonyl structure [ 11 ]. Isoxazolines can exhibit a variety of bioactivities, such as anti-inflammatory [ 12 ], anticancer [ 13 ], hypoglycemic [ 14 ], antibacterial [ 15 ], anti-HIV [ 16 ], anti-Alzheimer’s [ 17 ], antifungal [ 18 ], antimalarial [ 19 ], antioxidant [ 20 ], anti-tuberculosis [ 21 ], and antinociceptive [ 22 ] activities ( Figure 1 ). Isoxazolines can also be good herbicides [ 23 ] and insecticides [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our review of the literature, isoxazolines are heterocyclic compounds that are considered to be among the most potent antimicrobial agents. [23][24][25][26][27] However, studies on antitubercular agents containing an isoxazoline nucleus are scarce. In addition, the literature does not contain a molecular modelling study on isoxazoline derivatives as InhA inhibitors.…”
Section: Introductionmentioning
confidence: 99%